Influência das comorbidades na capacidade funcional de pacientes com artrite reumatoide - Marques, Wanessa Vieira (2014)
Patients with rheumatoid arthritis (RA) present higher prevalence of comorbidities. Such comorbidities are associated with different outcomes in RA patients, such as mortality risk, increase in disability, impact on RA specific treatment and higher medical costs. The purpose of this study was to assess the influence of comorbidities on the functional capacity and mobility of the affected individuals, and to identify, among the comorbidity indicators, the most appropriate to determine association between comorbidities and physical function on these patients. In a cross-sectional study we included 60 patients with RA fulfilling the American College of Rheumatology criteria (ACR, 1987) over a period of 11 months, both male and female between 43 and 80 years old. Comorbidities were assessed by means of three indicators: (i) total number of comorbidities (NCom) reported by the patients and listed on their medical records; (ii) the Charlson comorbidity index (CCI); and (iii) the functional comorbidity index (FCI). The activity of disease was evaluated by the Disease Activity Score, based on 28 joints and erythrocyte sedimentation rate value (DAS28/ESR). The participants’ functional capacity was measured using the Health Assessment Questionnaire (HAQ), and their mobility was measured using the chairrising test (CRT) and timed get up and go (TUG) test. Statistical analysis was performed using Log-Linear Stepwise multiple regression at 5% significance level. The prevalence of comorbidities in the investigated sample of patients with RA was 90% when the total number of comorbidities (NCom) was taken into consideration. In the final multiple regression model, the independent factors that influenced functional capacity (HAQ) were activity of disease (DAS28/ESR) and comorbidities, as assessed by FCI, which explained together 32.9% of the HAQ score variability (adjusted coefficient of determination [R2] = 0.329). With respect to the participants’ mobility (CRT and TUG), in the final model, only the independent factor comorbidities (FCI) exerted a significant influence on the results. The FCI scores explained 19.1% of the CRT variability (R2= 0.191) and 19.5% of the TUG variability (R2= 0.195). Among the comorbidity indicators used, the FCI was the main responsible for explain the physical function (HAQ) and mobility (CRT and TUG) variability at the final model in our sample. Comorbidities were highly prevalent in individuals with RA and exerted a negative influence on their functional capacity and mobility. FCI proved to be appropriate to determine the association between comorbidities and physical function in individuals with RA.